Evolution of External Consultant Involvement in Human Resource Management in Eastern Europe (1990-2007) - Poór, József; Józsa, Imola (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
This paper aims to analyze the evolution of Human Resources (HR) consulting in transitional economies of Eastern Europe (EE) from the political changes till the economic crisis (2008). This article provides insights into the specific socio-economic environment and HR practice of the region. Following Markham’s model (1999) we analyze specific characteristics of four typical ways of external consultant involvement: informative-becnhmarking, design, change and organizational learning consulting. in this region. In general, before the political changes at the end of the 1980’s, in most EE countries , consulting service was redendered by sector research institutes, controlled by the state or by the different minsitries. Consulting approach in EE countries were predominant similar to the school of scientific management. HR consulting hardly existed that time. Since changes in the regime’s consulting linked to privatization, firm restructuring, and development has been developing significantly in all countries of the region. HR consulting underwent a significant development in the region.